Mejoramiento y tecnificación de máquina extrusora para la elaboración de ladrillos artesanales - Cún Sánchez, Mery Felicia (2010)
In our country, Ecuador, there is community of makers of bricks. The present report intents to improve the process of elaboration of bricks through the improvement of an extruder machine, shaping of the cross section of a material by forcing it through a rigid die, to perfect the physics and mechanicals properties of bricks. This job analyze the design parameters of extruder machine using the fundaments of Mechanical Design, taking into account the requirements of bricks such as size and mechanicals and physics properties.